Patterns, treatments, and prognosis of tumor recurrence after resection for hepatocellular carcinoma with microvascular invasion: a multicenter study from China. Issue 7 (July 2022) - Chen, Zhen-Hua; Zhang, Xiu-Ping; Feng, Jin-Kai; Li, Le-Qun; Zhang, Fan; Hu, Yi-Ren; Zhong, Cheng-Qian; Wang, Kang; Chai, Zong-Tao; Wei, Xu-Biao; Shi, Jie; Guo, Wei-Xing; et al.
Abstract: Background: Microvascular invasion (MVI) is a risk factor of post-hepatectomy tumor recurrence for hepatocellular carcinoma (HCC). The patterns, treatments, and prognosis have not been documented in HCC patients with MVI. Methods: A multicenter database of patients with HCC and MVI following resection was analyzed. The clinicopathological and initial operative data, timing and first sites of recurrence, recurrence management, and long-term survival outcomes were analyzed. Results: Of 1517 patients included, the median follow-up was 39.7 months. Tumor recurrence occurred in 928 patients, with 49% within 6 months of hepatectomy and 60% only in the liver. The incidence of intrahepatic only recurrence gradually increased with time after 6 months. Patients who developed recurrence within 6 months of hepatectomy had worse survival outcomes than those who developed recurrence later. Patients who developed intrahepatic only recurrence had better prognosis than those with either extrahepatic only recurrence or those with intra- and extrahepatic recurrence. Repeat resection of recurrence with curative intent resulted in better outcomes than other treatment modalities. Conclusion: Post-hepatectomy tumor recurrence in patients with HCC and MVI had unique characteristics and recurrence patterns. Early detection of tumor recurrence and repeat liver resection with curative intent resulted in improved long-term survival outcomes.